The Struggle of Waste Pickers in Colombia: From being considered trash, to being recognised as workers - Parra, Federico (Anti-Trafficking Review, 2020)
Organised waste pickers in Colombia are formally recognised as subjects of special protection and as providers of the public service of recycling. As a consequence, they now receive remuneration for their work, but this was not always the case. This article highlights the strategies waste pickers used to successfully demand their rights while exploring the tensions and contradictions surrounding the formalisation of waste pickers as public service providers of recycling. These include a lack of sufficient guarantees from the government, attempts by private companies to appropriate waste pickers’ benefits, and a lack of respect by both the state and private businesses for the recognition of their rights in law. It concludes that there is an inherent tension between the main objectives of the waste pickers—to improve their working conditions and overcome poverty and vulnerability—and that of the state, which promotes free market competition in the provision of public services.